Joule heating of dry textiles made of recycled carbon fibers and PA6 for the series production of thermoplastic composites. (March 2020) - Reese, Julian; Vorhof, Michael; Hoffmann, Gerald; Böhme, Kurt; Cherif, Chokri
Processing carbon fiber reinforced thermoplastic parts includes heating to form the thermoplastic matrix. The needed heat can be applied externally or internally to the preform. One possibility to generate intrinsic heat involves the use of carbon fibers as a resistive element to induce joule heat. So far, most research efforts have been based on contacting continuous carbon fibers on both ends to melt the thermoplastic matrix of a pre-impregnated preform. The objective of this project is to use a dry hybrid yarn textile in a one-step process to impregnate and rapidly consolidate the dry textile in less than a minute. The desired molding process is based on joule heating of carbon fibers due to an applied current in the transverse fiber direction. This article focuses on the detection of the involved macroscopic parameters. The first composites produced by means of this new method exhibit a high potential with heating times of 15 s, a void fraction below 1%, and flexural properties comparable to the state of the art.